2021
DOI: 10.1093/bfgp/elab003
|View full text |Cite
|
Sign up to set email alerts
|

The non-coding epitranscriptome in cancer

Abstract: Post-synthesis modification of biomolecules is an efficient way of regulating and optimizing their functions. The human epitranscriptome includes a variety of more than 100 modifications known to exist in all RNA subtypes. Modifications of non-coding RNAs are particularly interesting since they can directly affect their structure, stability, interaction and function. Indeed, non-coding RNAs such as tRNA and rRNA are the most modified RNA species in eukaryotic cells. In the last 20 years, new functions of non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 138 publications
0
3
0
Order By: Relevance
“…IVT 7SK, we used 500ng of unmodified IVT RNA prepared as described above, using the adapter complementary to the 3′end of 7SK. m 6 A RNA immunoprecipitation and qRT-PCR. Cell nuclei were obtained from MOLM13 WT (six independent biological replicates) or METTL3-KD cells (six independent biological replicates for each shRNA) six days after doxycycline administration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IVT 7SK, we used 500ng of unmodified IVT RNA prepared as described above, using the adapter complementary to the 3′end of 7SK. m 6 A RNA immunoprecipitation and qRT-PCR. Cell nuclei were obtained from MOLM13 WT (six independent biological replicates) or METTL3-KD cells (six independent biological replicates for each shRNA) six days after doxycycline administration.…”
Section: Methodsmentioning
confidence: 99%
“…It is deposited mainly by the METTL3/METTL14/WTAP complex and has a variety of functions such as regulation of nuclear export, translation, and degradation of RNAs 4 , 5 . Other modifications, including Inosine (I), 5-methylcytosine (m5C), pseudouridine (Ψ) N6,N6-dimethyladenosine (m6,2A), 1-methylguanosine (m1G), 2′-O methyladenosine (2′-OMeA), and 7-methylguanosine (m7G), are increasingly recognized as important for the regulation of different RNAs in physiological and pathological contexts, including cancer 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic modification of RNA enables cells to respond rapidly to changes in the external environment, and the ability to adapt to changing microenvironments (such as stimuli and stress) is critical for tumor cell survival. Recent research has demonstrated that RNA modification has become a main emerging regulator in cancer by regulating various RNA metabolic processes ( Cui et al, 2017 ; Barbieri and Kouzarides, 2020 ; Miano et al, 2021 ). More and more evidence has shown that the abnormal expression of various m6A regulatory proteins plays a role in promoting or suppressing tumors in human tumors ( Nombela et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%